2003
DOI: 10.1128/jcm.41.1.324-329.2003
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of the Performance of Vibrational Spectroscopies for Rapid Identification of Bacterial and Fungal Pathogens Recovered from Blood Cultures

Abstract: Rapid identification of microbial pathogens reduces infection-related morbidity and mortality of hospitalized patients. Raman spectra and Fourier transform infrared (IR) spectra constitute highly specific spectroscopic fingerprints of microorganisms by which they can be identified. Little biomass is required, so that spectra of microcolonies can be obtained. A prospective clinical study was carried out in which the causative pathogens of bloodstream infections in hospitalized patients were identified. Referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
208
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(218 citation statements)
references
References 24 publications
4
208
0
6
Order By: Relevance
“…[5][6][7][8][9][10] Raman and infrared vibrational spectroscopic techniques have also been exploited for investigating eukaryotic and prokaryotic cells. [11][12][13][14][15] As can be seen from the literature, among these two methods, infrared, probably due to its higher sensitivity, has been most widely used. Several successful Fourier transform infrared (FTIR) studies for discrimination of Pap smear and other exfoliated cells have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Raman and infrared vibrational spectroscopic techniques have also been exploited for investigating eukaryotic and prokaryotic cells. [11][12][13][14][15] As can be seen from the literature, among these two methods, infrared, probably due to its higher sensitivity, has been most widely used. Several successful Fourier transform infrared (FTIR) studies for discrimination of Pap smear and other exfoliated cells have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous advantages of using this method of discrimination over traditional microbiological and molecular techniques are documented; these include speed, minimal sample preparation, automation and relatively low expense. The use of multivariate statistical techniques to analyse the infrared spectra has proved successful in the discrimination of the bacteria to subspecies levels (Maquelin et al, 2003;Naumann et al, 1991;Timmins et al, 1998;Winder et al, 2004). To date, the discrimination of members of the Mycobacterium genus by FT-IR has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Raman spectroscopy has been described as a promising tool [47,48]. Raman spectroscopy is a fast and reproducible typing technique, which provides strain-specific optical fingerprints in a few minutes instead of several hours to days, …”
Section: New Techniquesmentioning
confidence: 99%